Hegel y el fin de la historia - Pérez Rodríguez, Berta (Revista de Filosofía, 2003)
This paper connects Hegel’s philosophy of history with the problems posed by the Modern Age within the framework of the question of freedom. On the one hand I try to clarify to which extent the dialectical conception of history that Hegel proposes involves a real turn with regard to the inherited understanding of history; but, on the other hand, I inquire whether the persistent adherence of Hegel’s philosophy to the Modern Age makes it possible or rather impossible for his historical dialectics to account for the real, i. e., qualitative historical change.
Keywords: History; dialectics; idealism; freedom; Modern Age